The effects of household characteristics on the acquisition of life insurance: the case of Sabah - Zatul Karamah A.B.U.; Lim Thien Sang; Zaiton Osman; Amer Azlan Abdul Jamal; Rosle Mohidin (Universiti Malaysia Sabah, 2014)
Life insurance policies can be an element of a retirement plan to ensure financial stability after a person retires. However to date, most research conducted from the perspectives of the Malaysian market are focused only on the effect of economic variables rather than any other explanatory factors especially the non-economic variables towards the acquisition of life insurance by household in this country (Ahmad, Lim & Abdul Jamal, 2011; Redzuan, Abdul Rahman & S.H. Aidid, 2009; Ahmad & Yaakob, 2005). In line to address the gap, this research is expected to address the following objectives that are to examine the influence of socioeconomic variables, financial status, savings attitudes and the type of life insurance towards the acquistion of life insurance by households in the state of Sabah. The analytical approach is based on the model by Ferber and Lee (1980) and the Consumer Expenditure Surveys (2011) whereby a multiple regression function of a linear model is constructed to test the effects of the independent variables consisted of non-economic factors on the life insurance acquisition. This research suggests that the acquisition is contributed by the occupation, level of education, ownership of house and/or credit card and budget attitude. Also, two other independent variables namely the Financial Status and the Type of Life Insurance seem influential in affecting the life insurance acquisition. Overall, the results from this study seem to conform to those expected of rational insurance consumers.